CAUSES OF GASTRIC CANCER RECURRENCES IN PATIENTS AFTER RADICAL SURGERY - A. G. Baryshev; V. A. Porhanov; A. J. Popov; A. N. Lischenko; N. V. Khachaturyan; D. A. Valyakis; M. V. Bodnya (Инновационная медицина Кубани)
Gastric cancer is one the most serious oncological pathologies and it occupies the third position in the structure of oncological mortality. Latest achievements in surgery for gastric cancer are linked to extended lymph node dissection (D2), still, long-term results depend on carcinoma extension, regional lymph node involvement, tumor invasion depth and differentiation. Background: study survival in the patients treated for locally advanced gastric cancer regarding lymph node dissection volume and specific tumor characteristics. Materials and methods: applying Kaplan-Meier method and variance analysis we studied long-term results of 662 patients with gastric cancer with minimal lymph node dissection (D1) in the control group and extended lymph node dissection (D2) in the main group depending on 10 different features of tumor stage. Results: while analyzing long-term results of treatment we defined authentic advantage in patients in the main group according to their total and non-recurrent 5-year survival rates, and the median in the control group was 32,0 months, and in the main group it was 46,0 months. Inherent effect of extended lymph node dissection (D2) was defined at the level of any tumor characteristics, meanwhile their impacts including stage, metastatic spread and regional lymph node invasion and low tumor differentiation had more massive influence on patient survival rate than extended lymph node dissection. Conclusions: surgery for gastric cancer should be accompanied by extended lymph node dissection (D2), and its impact is seen at any tumor clinic stage. The best observed treatment effect in patients with gastric cancer could be achieved while following therapy standards and diagnosing tumors at early stages.